2011
DOI: 10.1042/cs20110378
|View full text |Cite
|
Sign up to set email alerts
|

Placental DEPTOR as a stress sensor during pregnancy

Abstract: DEPTOR [DEP-domain-containing and mTOR (mammalian target of rapamycin)-interacting protein] is a modulator of mTOR signalling that binds to mTORC (mTOR complex) 1 and mTORC2. However, to date, the precise functions of DEPTOR are not fully elucidated, particularly in reproductive tissues where mTOR acts as a placental nutrient sensor. Pregnancy is associated with major physiological and psychosocial changes and adaptation to these changes is crucial for normal fetal development. In the present study, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Elevated endogenous levels of glucocorticoid in the rat have been shown to suppress mTOR signaling in skeletal muscle (356). A recent study on human term placentas in women with self-reported high levels of environment-related stressful conditions during pregnancy showed a significant downregulation of Dishevelled, Egl-10, and Pleckstrin domain-domain-containing and mTOR-interacting protein (DEPTOR) as a modulator of mTOR signaling (357). There are currently no data regarding antenatal glucocorticoid exposure and placental mTOR signaling.…”
Section: Placental Sensing Mechanismsmentioning
confidence: 99%
“…Elevated endogenous levels of glucocorticoid in the rat have been shown to suppress mTOR signaling in skeletal muscle (356). A recent study on human term placentas in women with self-reported high levels of environment-related stressful conditions during pregnancy showed a significant downregulation of Dishevelled, Egl-10, and Pleckstrin domain-domain-containing and mTOR-interacting protein (DEPTOR) as a modulator of mTOR signaling (357). There are currently no data regarding antenatal glucocorticoid exposure and placental mTOR signaling.…”
Section: Placental Sensing Mechanismsmentioning
confidence: 99%
“…Mammalian Target of Rapamycin (mTOR), an intracellular nutrient stress sensor in the placenta (Roos et al, 2009) has been linked to the downstream signalling of both glucocorticoids (Jellyman et al, 2012) and IGF2 (Dai et al, 2011). A small study reporting a lower placental DEP domaincontaining mTOR-interacting protein (DEPTOR) in mothers with higher perceived life stress and reduced DEPTOR following increased cortisol in vitro (Mparmpakas et al, 2012) suggests further investigation of these genes is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Raw CT values were processed using the DCT method relative to the geometric mean of two reference genes, ACTB and GAPDH. These reference genes have been widely utilized in other studies of choriocarcinoma cell line mRNA expression levels (Lee et al, 2004;Chiu et al, 2007;Li et al, 2008;Masumoto et al, 2011;Mparmpakas et al, 2012;Chen et al, 2013). DCT values generated relative to ACTB and GAPDH were highly correlated in all assays included in this study (Supplementary data, Fig.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 90%